Hubungan Asupan Energi dan Protein dengan Status Gizi pada Penderita Gagal Ginjal Kronik yang Menjalani Hemodialisa Rawat Jalan di RSUD Tugurejo Semarang - Nihaya Ika Fahmia; Tatik Mulyati; Erma Handarsari (Universitas Muhammadiyah Semarang, 2012)
Chronic renal failure is the final stage renal disease is a progressive disorder of renal function and irreversible. Where is the ability of the body fails to maintain metabolism and fluid and electrolyte balance, causing uremia. Dialysis can be done in several ways, and in general use thehemodialysis. Nutritional status in patients with chronic renal failure with hemodialysis for 18-56% of energy and protein deficiency. chronic renal failure undergoing hemodialysis should receive energy and protein intake sufficient as needed to achieve and maintain optimal nutritional status. The purpose of this study was to determine the relationship of energy and protein intake and nutritional status of patients with chronic renal failure hemodialysis.This research is an explanation or explanatory research. The method used is a cross sectional survey approach. Number of samples 33 people consisting of outpatients Tugurejo Public Hospital Semarang. The study starts from proposal writing through the writing of the month from January to July 2012. Univariate analysis performed to present the frequency distribution. Test normality of the data is done by Kolmogorov-Smirnov test. Bivariate analysis to examine the relationship between dependent and independent variables with the Spearman Rank-Correlation.The results showed that the samples of chronic renal failure hemodialysis largely male sex is 20 samples (60.6%) by age group, while most are aged 46-60 years ie 16 samples (48.5%). For the highest level of education is elementary that 15 samples (45.5%), private sector employment is highest at 13 samples (39.4%), the majority of normal nutritional status ie 17 samples (51.5%), the majority of normal energy intake is 17 samples (51.5%) and the majority of normal protein intake is 17 samples (51.5%). Statistical analysis showed an association between energy intake and nutritional status with a p-value 0.000 and r = 0.772 and the relationship of protein intake and nutritional status premises p-value 0.000 and r = 0.633Keywords : Intake energy, protein and nutritional status